Fluoride content of tank water in Australia. (June 2014) - Cochrane, NJ; Hopcraft, MS; Tong, AC; Thean, HL; Thum, YS; Tong, DE; Wen, J; Zhao, SC; Stanton, DP; Yuan, Y; Shen, P; Reynolds, EC
Abstract Background The aims of this study were to: (1) analyse the fluoride content of tank water; (2) determine whether the method of water collection or storage influenced fluoride content; and (3) survey participant attitudes towards water fluoridation. Methods Plastic tubes and a questionnaire were distributed through dentists to households with water tanks in Victoria. A midstream tank water sample was collected and fluoride analysed in triplicate using ion chromatography Results All samples (n = 123) contained negligible amounts of fluoride, with a mean fluoride concentration of <0.01 ppm (range: <0.01–0.18 ppm). No statistically significant association was found between fluoride content and variables investigated such as tank material, tank age, roof material and gutter material. Most people did not know whether their tank water contained fluoride and 40.8% preferred to have access to fluoridated water. The majority thought fluoride was safe and more than half of the respondents supported fluoridation. Fluoride content of tank water was well below the optimal levels for caries prevention. Conclusions People who rely solely on tank water for drinking may require additional exposure to fluoride for optimal caries prevention.